Aspects of Pedagogical Interaction in the Formation of Personal Meaning of a Literary Work at Preschool Age - Freiberga, Inese (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Personal meaning is not limited to the subjective significance of processes, things and occurrences, but it has a personal significance in the life of an individual. It influences his or her conduct, behaviour and the course of personal development by changing facts, norms and generally accepted meanings and symbols into an influential factor of development. The genesis of personal meaning determines the organization and the nature of pedagogical process of familiarization with a literary work. Pedagogical thinking has accumulated a wide range of knowledge about the role of fiction in development of personality. However the role of personal meaning in relation to literary text and its impact upon a child's activities, conduct and behavior studies has rarely been discussed. Also, in practical teaching of literary works the process itself might not always facilitate the formation of personal meaning of a text. The article deals Aspects of Pedagogical Interaction in the Formation of Personal Meaning of a Literary Work at Preschool Age.